Pengembangan Modul Ajar Numerasi Berbasis Etnomatematika pada Siswa Sekolah Dasar - Kasmilawati, Kasmilawati; Ma’rufi, Ma’rufi; Patmaniar, Patmaniar (Universitas Cokroaminoto Palopo, 2025)
This study aimed to develop and examine the effectiveness of a numeracy teaching module based on an ethnomathematics approach in improving elementary school students' numeracy skills. The research employed a Research and Development (R&D) approach using the 4D development model (Define, Design, Develop, Disseminate). The sample consisted of all 35 fifth-grade students at UPT SD Negeri 040 Salulemo. Data were collected through expert validation, teacher and student response questionnaires, observation of module implementation, and effectiveness testing using paired t-tests and gain analysis. The validation results showed that the module had very good quality and was deemed suitable for use (average expert validation score of 82.33%). The responses from students and teachers indicated that the numeracy module based on the ethnomathematics approach was highly practical (with an average student response score of 86.87% and an average teacher response score of 90.63%). The effectiveness test revealed a significant improvement in students' numeracy skills after using the module, with n-gain scores categorized as moderate to high, indicating that the module was effective in learning. This study contributes theoretically to the development of ethnomathematics-based mathematics education and provides practical benefits as a relevant instructional guide for teachers and students.